WIPI2 enhances the vulnerability of colorectal cancer cells to erastin via bioinformatics analysis and experimental verification - Yu, Liying; Luo, Yan; Ding, Xile; Tang, Miaomiao; Gao, Huan; Zhang, Renfang; Chen, Mingfu; Liu, Yuchen; Chen, Qiongxia; Ouyang, Yanli; Wang, Xiang; Zhen, Hongyan (Frontiers in Oncology, 2023)
Introduction WD Repeat Domain Phosphoinositide Interacting 2 (WIPI2) is a WD repeat protein that interacts with phosphatidylinositol and regulates multiprotein complexes by providing a b-propeller platform for synchronous and reversible protein-protein interactions assembled proteins. Ferroptosis is a novel iron-dependent form of cell death. It is usually accompanied with the accumulation of membrane lipid peroxides. Our study is to focus on investigating the effect of WIPI2 on the growth and ferroptosis of colorectal cancer (CRC) cells and its potential mechanism. Methods We analyzed the expression of WIPI2 in colorectal cancer versus normal tissues through The Cancer Genome Atlas (TCGA), and the relationship between clinical traits and WIPI2 expression and prognosis was assessed by univariate and multifactorial cox analysis. Next, we constructed the siRNAs targeting the WIPI2 sequence si-WIPI2 to further investigate the mechanism of WIPI2 in CRC cells through vitro experiments. Results Public data from the TCGA platform showed that WIPI2 expression was significantly elevated in colorectal cancer tissues compared to paracancerous tissues, and high WIPI2 expressionpredicted poor prognosis for CRC patients. Moreover, we found that the knockdown of WIPI2 expression could inhibit the growth and proliferation of HCT116 and HT29 cells. Furthermore, we found that the expression level of ACSL4 decreased and that of GPX4 increased when WIPI2 was knocked down, suggesting that WIPI2 can potentially positively regulate CRC ferroptosis. Meanwhile, both NC and si groups were able to further inhibit cell growth activity, as well as increase WIPI2 and decrease GPX4 expression when treated with Erastin, but the rate of cell viability inhibition and the trend of protein changes were more significantly in the NC group than si groups, which indicated that Erastin induced CRC ferroptosis through the WIPI2/GPX4 pathway thereby enhancing the sensitivity of colorectal cancer cells to Erastin. Conclusions Our study suggested that WIPI2 had a promotional effect on the growth of colorectal cancer cells, and it also played an important role in the ferroptosis pathway.